Penentuan Kadar Senyawa Fenolat Dan Uji Aktivitas Antioksidan Pada Buah Terung Belanda (Cyphomandra betacea (Cav.) Sendtn) Secara Spektrofotometri Visibel - Fithriani Armin; Yuli Yani Dewi; Mahyuddin Mahyuddin (Jurnal Farmasi Higea, 2011)
Levels Determination of phenolic compounds and antioxidant activity assay of eggplant belanda fruit (Cyphomandra betacea (Cav.) Sendtn) with  visible spektofotometri has  been done. Determination of phenolic compounds performed by the method of Folin ciocalteu, while DPPH is used as an antioxidant. The antioxidant activity is determined by its IC50 value. In this treatment gallic acid used as a comparison. The results showed that the levels of phenolic compounds from the sample extract solution is 0.288845 mg / g; 0.29678 mg / g and 0.28964 mg / g respectively. The antioxidant activity determined by IC50 values, where the value of its IC50 was 240.0811 µg / mL; 204.5010 µg / mL; 196.8531 µg / mL.